Alginate-Based Platforms for Cancer-Targeted Drug Delivery. (7th October 2020) - He, Lili; Shang, Zhenghui; Liu, Hongmei; Yuan, Zhi-xiang
Abstract : As an acidic, ocean colloid polysaccharide, alginate is both a biopolymer and a polyelectrolyte that is considered to be biocompatible, nontoxic, nonimmunogenic, and biodegradable. A significant number of studies have confirmed the potential use of alginate-based platforms as effective vehicles for drug delivery for cancer-targeted treatment. In this review, the focus is on the formation of alginate-based cancer-targeted delivery systems. Specifically, some general chemical and physical properties of alginate and different types of alginate-based delivery systems are discussed, and various kinds of alginate-based carriers are introduced. Finally, recent innovative strategies to functionalize alginate-based vehicles for cancer targeting are described to highlight research towards the optimization of alginate.